Komunitas Anak Alam sebagai Gerakan Sosial Baru dalam Mencegah Angka Putus Sekolah di Kabupaten Bangli - Putri Djafarnantyo, Raghia Khasana; Punia, I Nengah; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This research seeks to discuss and explain about Anak Alam Community as new social movement in preventing dropout rates in Bangli Regency. This research uses descriptive-explanative qualitative research methods with an explanatory analysis of the resource mobilization theory of Anthony Oberschall. According to the resource mobilization theory can be summarized the main factors in social movement, namely: (1) organization of social movement, (2) leaders and leadership, (3) resource and resource mobilization, (4) network and participation, (5) opportunitues and capacities of the community. Based on the result of this study, it is known that the Anak Alam Community has that factor that cause Anak Alam Community can survive until this day. Keywords: Anak Alam Community, New Social Movement, Dropout Rates